Pengaruh produk domestik regional bruto dan upah minimum terhadap penyerapan tenaga kerja di kota samarinda - Nur Kasanah; Muhammad Saleh; Muliadi Muliadi (Jurnal Ilmu Ekonomi Mulawarman (JIEM), 2020)
The research entilted â€œThe gross regional domestic bruto and the minimum wage for absorption of labor in Samarinda â€. It aims to find out about the gross regional domestic bruto and the minimum wage for absorption of labor in Samarinda during the research year. As for the data used in this study is secondary data taken from the labor offices and central statistics agency (BPS).In the research, the secondary data is collapsed time or the the time series, analyzed using a multiple regression analysis tool. The hypothetically testing uses classical assumption test, test R and R2, which have already adapted the F and T and quantitaive analysis using the computer SPSS program 21. The study shows that gross regional domestic bruto has a positive and significant impact on the worforce being absorted in Samarinda and minimum wage has a positive and insignificant effect on workforce absortion in Samarinda